What about healthy participants? The improvement and deterioration of self-reported health at a 10-year follow-up of the Västerbotten Intervention Programme - Yulia Blomstedt; Maria Emmelin; Lars Weinehall (Taylor & Francis Group, 2011)
The Västerbotten Intervention Programme (VIP) addresses cardiovascular disease and diabetes in the middle-aged population of Västerbotten County, Sweden. Self-reported health (SRH) is one of the risk factors for both conditions. The aim of this study was to analyse the development patterns of SRH among the VIP participants.Cross-sectional data from 1990 to 2007 were used to analyse the prevalence of poor SRH among 101,396 VIP participants aged 40–60 years. Panel data were used to study the change in SRH among 25,695 persons aged 30–60 years, who participated in the VIP twice within a 10-year interval.Prevalence of poor SRH fluctuated between 1990 and 2007 in Västerbotten County. There was a temporary decline around 2000, with SRH continuously improving thereafter. The majority of panel participants remained in good SRH; over half of those with poor or fair SRH at baseline reported better SRH at follow-up. SRH declined in 19% of the panel participants, mostly among those who had good SRH at the baseline. The decline was common among both women and men, in all educational, age and marital status groups.The SRH improvement among those with poor and fair SRH at baseline suggests that VIP has been successful in addressing its target population. However, the deterioration of SRH among 21% of the individuals with good SRH at baseline is of concern. From a public health perspective, it is important for health interventions to address not only the risk group but also those with a healthy profile to prevent the negative development among the seemingly healthy participants.